A remarkable new species of Davilla Vand. (Dilleniaceae, Dolicocarpoideae) from the Brazilian Savanna supported by morphological and anatomical data - Silva, Marcos José Da; Santos, Igor Soares Dos (Phytotaxa, 2022)
Davilla pygmaea, a new species endemic to the Brazilian Savanna, is described, illustrated and its systematic position is discussed here. The new species is closely related to D. elliptica and D. grandiflora, from which it differs by characters such as a decumbent habit, the shape of its leaf blades, the inflorescence architecture, the size and numbers of flowers, the size of the internal and external sepals during flowering and fruiting, the androecium with 126-131 stamens, and the presence and type of trichomes on vegetative organs. Anatomical characters such as the number of vascular bundles in the petiole and midrib, shape of the midrib in cross section, the margins of the leaf blades, the presence and arrangement of the fibers associated with small-caliber vascular bundles, and the presence of a fiber sheath extension in studied species also differentiate them. Histochemical tests demonstrated that alkaloids, acidic lipids, and phenolic compounds present in the leaf tissues of the new species and D. grandiflora, its closest congener, may have potential medicinal properties. In addition, the new species has its distribution mapped, its flowering and fruiting seasons delimited, and would likely be considered Critically Endangered (CR), as we have found only two populations. A key to identify Davilla species known to Goiás State, Brazil, is provided.